Preparation method of high-strength and high-plasticity additive manufacturing nickel-based superalloy

By using solid solution + double-stage aging treatment process in the additive manufacturing of nickel-based high-temperature alloys, a multi-scale heterostructure is formed, which solves the problem of difficult coordination between strength and plasticity after heat treatment of nickel-based high-temperature alloys in the prior art, and significantly improves the strength and elongation of the alloy.

CN119525521AActive Publication Date: 2025-02-28CENT SOUTH UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411793963.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-02-28
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The prior art After heat treatment of additively manufactured nickel-based high-temperature alloys, it is difficult to achieve the coordination of alloy strength and plasticity, and it is easy to lead to plastic loss or cracking.

Method used

Using solid solution + double-stage aging treatment process, a multi-scale heterostructure consisting of bimodal size distribution grains, nanosecond phase and nano defects are formed through solid solution treatment of 1160-1220℃ and a double-stage aging treatment of 843℃/4 h + 760℃/8 h.

Benefits of technology

The excellent strong plastic synergistic effect of nickel-based high-temperature alloy is achieved, with a yield strength of 1281 MPa, a tensile strength of 1609 MPa, an elongation of 16.6%, and a cracking risk is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-strength and high-plasticity additive manufacturing nickel-based high-temperature alloy. Through solid solution and two-stage aging heat treatment, the problems of high strength and low plasticity caused by heat treatment of the precipitation strengthening nickel-based superalloy are effectively solved, and the high-performance nickel-based superalloy with the tensile strength of 1609 MPa and the elongation of 16.6% is obtained. Solution treatment at the temperature of 1160-1200 DEG C is utilized for the first time, then a two-stage aging heat treatment process at the temperature of 843 DEG C / 4 h and 760 DEG C / 8 h is carried out, and a heat treatment state product which is of a multi-scale heterostructure composed of bimodal size distribution crystal grains, a nano second phase, nano defects and the like and has excellent high plasticity is prepared. The preparation process is simple, controllable and adjustable, the obtained product is excellent in performance, and large-scale industrial application is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high-temperature alloys and additive manufacturing, and relates to a heat treatment process for a high-strength and plastic nickel-based high-temperature alloy for additive manufacturing. Background Art

[0002] Nickel-based superalloys have excellent strength, damage tolerance and durability, and are the preferred structural materials for hot-end components of aerospace. As one of the advanced additive manufacturing technologies, laser powder bed fusion (PBF-LB) can achieve integrated forming of parts with complex geometries and has become a key development technology and cutting-edge direction in aerospace manufacturing. However, the extremely fast solidification rate (10 6 -10 8 K / s) will inhibit the precipitation of strengthening phases and fail to give full play to the strengthening effect of the main strengthening phases in precipitation-strengthened nickel-based superalloys. Therefore, it is necessary to perform subsequent heat treatment on the PBF-LB forming precipitation-strengthened nickel-based superalloys to release residual stress, fully precipitate the strengthening phases, and improve the microstructure and mechanical properties.

[0003] At present, the commonly used heat treatment process for additive manufacturing of nickel-based high-temperature alloys is usually solid solution + aging treatment. Hu [YongHu, Huibin Jia, Xu Zhang, et al., Delayed recrystallization behavior and deformation mechanism of IN738LC alloy prepared by laser powder bed fusion[J]. Materials Science & Engineering A, 2024, 903: 146697] et al. prepared IN738LC alloy by additive manufacturing, and the yield strength, tensile strength and elongation were 975 MPa, 1260 MPa and 16.8%, respectively; after 1250℃ / 2 h solid solution treatment and 850℃ / 2 h aging treatment, the yield strength, tensile strength and elongation of the alloy were 1305MPa, 14620MPa and 5.4%, respectively. Liu [Xinxin Liu, Rui Hu, Chenyu Yang, et al.,Microstructure evolution and strengthening mechanism of γ′-strengtheningsuperalloy prepared by laser powder bed fusion [J]. Materials Science &Engineering A, 2023, 871: 144915] et al. subjected Haynes 230 alloy prepared by additive manufacturing to a 1200℃ / 2 h solution treatment and a 750℃ / 24 h aging treatment. The yield strength, tensile strength and elongation of the alloy were 1245 MPa, 1468 MPa and 6.3%, respectively.Liang [Jiangkai Liang, Zhubin He, Wei Du et al., Tailoring the microstructure and mechanical properties of laser metal-deposited Hastelloy X superalloy sheets via post heat-treatment [J]. Materials Science & Engineering A, 2023, 884: 145546] et al. subjected the Haynes X alloy prepared by additive manufacturing to a solid solution treatment at 1175℃ / 1 h and a double-stage aging treatment at 720℃ / 8 h+620℃ / 8 h. The yield strength, tensile strength and elongation of the alloy were 355 MPa, 688 MPa and 47.4%, respectively. Our research group has previously developed a technology that uses in-situ heat treatment to improve the performance of 3D printed nickel-based superalloys. The resulting René104 alloy has a yield strength of 1017MPa, a tensile strength of 1242MPa, and an elongation of 11.1%. The René104 nickel-based superalloy with trace rare earth Sc added has a yield strength of 1145MPa and a tensile strength of 1252MPa [Liu Zuming, Wei Bing, Nong Bigong, et al., A method for improving the mechanical properties of 3D printed nickel-based superalloys by in-situ heat treatment [P]. Hunan Province: CN112008079B, 2020-08-30]. Moreover, further research by our research group found that after the René104 alloy was subjected to solution treatment (1160℃ / 1h) + aging treatment (820℃ / 8h+760℃ / 8h), the alloy cracked, and its yield strength, tensile strength and elongation were 1230MPa, 1298MPa and 2.62% [Wei Bing, Selective Laser Melting and Crack Suppression of René104 High-temperature Alloy [D], Changsha: Central South University, 2022].

[0004] It is not difficult to see from the above search results that it is difficult to achieve the synergy between alloy strength and plasticity after heat treatment of additively manufactured nickel-based high-temperature alloys, especially after heat treatment of precipitation-strengthened nickel-based high-temperature alloys, in the prior art. At the same time, more importantly, many additively manufactured nickel-based high-temperature alloys are very likely to cause plasticity loss or even cracking of the alloys during heat treatment. The present invention proposes to obtain a multi-scale heterogeneous structure composed of bimodal size distribution grains, nano-second phases and nano-defects through solid solution and two-stage aging heat treatment, which effectively solves the problem of high strength and low plasticity caused by the existing precipitation-strengthened nickel-based high-temperature alloy heat treatment. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention is based on the previous research of the inventor's team (CN112008079B) and designs a solid solution + two-stage aging treatment process for the first time, which can simultaneously improve the tensile strength and yield strength of the product while maintaining good elongation. Through process optimization, an additively manufactured nickel-based high-temperature alloy with excellent strength-plasticity synergistic effect is obtained for the first time.

[0006] The present invention provides a preparation method of a high-strength and plasticity additively manufactured nickel-based high-temperature alloy. The additively manufactured nickel-based high-temperature alloy is used as a raw material, and a multi-scale heterogeneous structure composed of bimodal size distribution grains, nano-second phases and nano-crystal defects is induced in the heat-treated alloy, thereby achieving an excellent synergistic effect of strength and plasticity.

[0007] The present invention discloses a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy, wherein the nickel-based high-temperature alloy is a René 104 alloy containing Sc and Y, and the René 104 alloy containing Sc and Y is prepared by additive manufacturing using René 104ScY alloy powder as a raw material; the mass percentage of Sc and Y in the René 104 alloy containing Sc and Y is 0.005wt.% to 0.01wt.%;

[0008] The laser additive manufacturing is:

[0009] Step 1: Using René104ScY alloy powder with designed composition as raw material, a printed product is prepared by laser powder bed fusion (PBF-LB) process; forming is performed by adopting the optimal process parameters of PBF-LB: controlling the laser input power to be 200-400 W, preferably 320-400 W, and more preferably 345-355 W, controlling the scanning speed to be 200-1200 mm / s, preferably 750-1200 mm / s, and more preferably 780-820 mm / s, the layer thickness to be 35-60 μm, and the rotation angle between adjacent layers to be 67°;

[0010] Step 2: taking the obtained printed product as the treatment object, performing a solid solution treatment at 1160-1220° C., preferably 1160-1200° C., for 50-240 min to obtain a solid solution product;

[0011] Step 3: The obtained solid solution product is treated as the treatment object, and the solid solution product is subjected to aging treatment. The aging conditions are: first aging treatment at a temperature of 830-850°C for 200-280 minutes, cooling to 755-765°C with the furnace, and then keeping the temperature for 450-500 minutes to obtain an aged product.

[0012] The present invention provides a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy, which is characterized in that the preparation method of the selected René104ScY alloy raw material powder is as follows:

[0013] According to the designed components, various raw materials are prepared, all raw materials are mixed, and alloy powder is prepared by a tightly coupled argon atomization system. The crucible is a graphite crucible, the melting temperature is 1600-1650°C, and the temperature is kept constant for 10-20 minutes. The gas pressure is 3-5 MPa; a vibration screening device is used to screen out René104ScY alloy powder with a particle size range of less than 100 μm, preferably 15-74 μm, as powder for laser additive manufacturing;

[0014] Preferably, Al-Sc master alloy is used to introduce Sc, and other raw materials can be single metals or master alloys.

[0015] The present invention provides a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy, characterized in that: the René 104Sc alloy raw material powder comprises the following components in terms of mass percentage:

[0016] Co: 21.4~21.6wt.%, Cr: 12.9~13.1wt.%, Mo: 3.7~3.9wt.%, Ti: 3.8~4.0wt.%, Al: 3.3~3.4wt.%, Ta: 2.2~2.3wt.%, W: 3.3~3.5wt.%, Nb: 0.8~1.0wt.%, C: 0.03~0.06wt.%, Zr: 0.04~0.06wt.%, B: 0.02~0.04wt.%, Sc+Y is 0.006~0.08wt.%, and the balance is Ni, and in molar ratio, Sc:Y is 1:1.

[0017] The present invention discloses a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy. In step 2, the printed product is used as a treatment object, and a solid solution treatment is performed at 1175-1185° C. for 60-120 min to obtain a solid solution product.

[0018] As a preferred method, the solid solution product is subjected to aging treatment, and the aging conditions are: first aging treatment at 843°C for 4 h, followed by furnace cooling to 760°C and then heat preservation for 8 h to obtain an aged product.

[0019] The present invention discloses a preparation method of a high-strength plastic additively manufactured nickel-based high-temperature alloy, wherein the yield strength of the printed product is 960-1059 MPa, the tensile strength is 1315-1405 MPa, and the elongation is 21.3-28.8%.

[0020] Preferably, in the present invention, the relative density of the printed product is higher than 99.8%, and the yield strength, tensile strength and elongation are 1059 MPa, 1405 MPa and 28.8%, respectively.

[0021] The preparation method of the René104ScY alloy raw material powder selected by the present invention is as follows:

[0022] According to the designed components, various raw materials are prepared, all raw materials are mixed, and alloy powder is prepared by a tightly coupled argon atomization system. The crucible is a graphite crucible, the melting temperature is 1600-1650°C, and the temperature is kept constant for 10-20 minutes. The gas pressure is 3-5 MPa; a vibration screening device is used to screen out René104ScY alloy powder with a particle size range of less than 100 μm, preferably 15-74 μm, as powder for laser additive manufacturing;

[0023] Preferably, Al-Sc master alloy is used to introduce Sc, and other raw materials can be single metals or master alloys.

[0024] Preferably, René104ScY alloy powder with designed composition is used as raw material powder, and the printed product is prepared by PBF-LB process; the optimal process parameters of PBF-LB are adopted for forming: laser power 350 W, scanning rate 800 mm / s, layer thickness 40 μm, serpentine scanning strategy, and rotation angle between adjacent layers is 67°; the sample is characterized in that the microstructure of the obtained product is mainly composed of equiaxed crystals and columnar crystals.

[0025] The present invention discloses a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy. The nickel-based high-temperature alloy is manufactured by additively manufacturing to obtain a printed product, and the printed product is subjected to heat treatment to obtain a heat-treated product.

[0026] The present invention provides a method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy.

[0027] After solution treatment at 1160℃ for 1 h and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1152 MPa, a tensile strength of 1464 MPa, and an elongation of 3.2%.

[0028] After solution treatment at 1180℃ for 1 h and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1281 MPa, a tensile strength of 1609 MPa, and an elongation of 16.6%.

[0029] After solution treatment at 1200℃ for 1 h and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1152 MPa, a tensile strength of 1402 MPa, and an elongation of 6.4%.

[0030] During the technical development process, it was also found that the microstructure of the alloy changes continuously with the increase of solution temperature; the higher the solution treatment temperature, the less obvious the molten pool boundary and cellular structure of the alloy. As the solution temperature increases further, obvious recrystallization and grain growth occur in the alloy.

[0031] The present invention discloses a preparation method of a high-strength and plastic additively manufactured nickel-based high-temperature alloy, wherein the heat-treated nickel-based high-temperature alloy has nano-defects; the nano-defects include at least one of nano-twins, high-density stacking faults and Lomer-Cottrell locks.

[0032] In the present invention, the yield strength and tensile strength of the product can be greatly increased by using appropriate parameters for solid solution + double-stage aging treatment.

[0033] The present invention develops for the first time a René104ScY alloy with excellent strength-plasticity synergistic effect. The René104ScY alloy designed and prepared by the present invention has an elongation greater than 16%, a yield strength greater than or equal to 1281 MPa, and a tensile strength greater than or equal to 1609 MPa.

[0034] The invention discloses a preparation method of a high-strength and plastic additively manufactured nickel-based high-temperature alloy. After a double-stage aging treatment, the obtained product contains a multi-scale heterogeneous structure composed of bimodal size distribution grains, a nano second phase and nano defects.

[0035] The material process design of the invention is reasonable, the requirements for the production process are reduced, and the prepared alloy parts have high strength and maintain high elongation, which provides the necessary conditions for its industrialization.

[0036] Compared with Chinese patent CN112008079B, the heat-treated additively manufactured nickel-based high-temperature alloy provided by the present invention has higher strength and elongation.

[0037] Principles and advantages

[0038] 1. This invention designs a preparation method for high-strength and plastic additive manufacturing nickel-based high-temperature alloy for the first time, and proposes for the first time to use a solid solution + two-stage aging process to heat treat the printed sample. After the designed heat treatment process is used, the sample produces at least one multi-scale heterogeneous structure including bimodal size distribution grains, nanophases and nanotwins, high-density stacking faults and Lomer-Cottrell locks, which effectively regulates the microstructure of the alloy.

[0039] 2. The present invention adopts a heat treatment process combining solution treatment and aging treatment with appropriate parameters, which successfully solves the problems of high strength, low plasticity and even cracking of high Al and Ti nickel-based high-temperature alloys after heat treatment in additive manufacturing. The yield strength reaches 1281 MPa, the tensile strength is 1609 MPa, and the elongation is 16.6%, achieving excellent strength-plasticity synergy.

[0040] 3. The components of the present invention are reasonably designed, and the preparation process is simple, controllable and adjustable. The obtained product has excellent performance. The sample after heat treatment has excellent mechanical properties, which is convenient for large-scale industrial application. It provides a new method for the development of high-performance nickel-based high-temperature alloys for additive manufacturing and their microstructure regulation. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0042] Figure 1 The microstructure EBSD analysis images and γ' phase morphology SEM images of the nickel-based high-temperature alloy after heat treatment in Examples 1 to 3 of the present invention;

[0043] Figure 2 The SEM and TEM images of the aging twins in Example 2 of the present invention;

[0044] Figure 3 The room temperature engineering stress-strain curves of the samples subjected to different heat treatments in Examples 1 to 3 of the present invention;

[0045] Figure 4 The microstructure EBSD analysis images and γ' phase morphology SEM images of the nickel-based high-temperature alloy after heat treatment in Comparative Examples 1, 2 and 3 of the present invention are shown;

[0046] Figure 5 The room temperature engineering stress-strain curves of the samples subjected to different heat treatments in comparative examples 1, 2 and 3 of the present invention. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0048] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0049] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0050] Embodiment 1:

[0051] (1) All raw materials were mixed and René104ScY alloy powder was prepared by a tightly coupled argon atomization system. The crucible was a graphite crucible, the melting temperature was 1600-1650°C, the temperature was kept constant for 10-20 min, and the gas pressure was 3-5 MPa. A vibration screening device was used to screen out René104ScY alloy powder with a particle size of 15-74 μm for laser additive manufacturing. The layer thickness was controlled to be 40 μm, the laser power was 350 W, the scanning rate was 800 mm / s, the interlayer rotation angle was 67°, and a serpentine scanning strategy was adopted.

[0052] The prepared René104ScY alloy powder comprises the following components in terms of mass percentage:

[0053] Co: 21.5±0.1wt.%, Cr: 13.0±0.1wt.%, Mo: 3.8±0.1wt.%, Ti: 3.9±0.1wt.%, Al: 3.35±0.05wt.%, Ta: 2.25±0.05wt.%, W: 3.4±0.1wt.%, Nb: 0.9±0.1wt.%, C: 0.045±0.015wt.%, Zr: 0.05±0.01wt.%, B: 0.03±0.01wt.%, Sc+Y is 0.007±0.001wt.% (the molar ratio of Sc:Y is 1:1), and the balance is Ni;

[0054] (2) The printed sample was vacuum sealed and solution treated at 1160°C, heated at a rate of 5°C / min, kept at this temperature for 1 h, and then taken out and cooled to room temperature;

[0055] (3) The solution treated sample was then subjected to a double-stage aging heat treatment at 843°C / 4 h + 760°C / 8 h, and after the treatment was completed, it was taken out and cooled to room temperature;

[0056] (4) After heat treatment, columnar crystals parallel to the construction direction are still retained in the sample;

[0057] (5) After heat treatment, two γ' phases of different sizes are formed in the sample;

[0058] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results showed that the yield strength was 1152 MPa, the tensile strength was 1464 MPa, the strength was significantly improved, the elongation was 3.2%, and the comprehensive mechanical properties were significantly better than those of the same grade and type of alloys.

[0059] Embodiment 2:

[0060] (1) All raw materials were mixed and René104ScY alloy powder was prepared by a tightly coupled argon atomization system. The crucible was a graphite crucible, the melting temperature was 1600-1650°C, the temperature was kept constant for 10-20 min, and the gas pressure was 3-5 MPa. A vibration screening device was used to screen out René104ScY alloy powder with a particle size of 15-74 μm for laser additive manufacturing. The layer thickness was controlled to be 40 μm, the laser power was 350 W, the scanning rate was 800 mm / s, the interlayer rotation angle was 67°, and a serpentine scanning strategy was adopted.

[0061] The prepared René104ScY alloy powder comprises the following components in terms of mass percentage:

[0062] Co: 21.5±0.1wt.%, Cr: 13.0±0.1wt.%, Mo: 3.8±0.1wt.%, Ti: 3.9±0.1wt.%, Al: 3.35±0.05wt.%, Ta: 2.25±0.05wt.%, W: 3.4±0.1wt.%, Nb: 0.9±0.1wt.%, C: 0.045±0.015wt.%, Zr: 0.05±0.01wt.%, B: 0.03±0.01wt.%, Sc+Y is 0.007±0.001wt.% (the molar ratio of Sc:Y is 1:1), and the balance is Ni;

[0063] (2) The prepared printed sample was sealed in a vacuum tube and solution treated at 1180°C. The temperature was increased at a rate of 5°C / min and kept at this temperature for 1 h. The sample was then taken out and cooled to room temperature.

[0064] (3) The solution treated samples were then subjected to a double-stage aging heat treatment at 843°C / 4 h + 760°C / 8 h. After the treatment, the samples were taken out and cooled to room temperature.

[0065] (4) After heat treatment, a large number of equiaxed crystals were formed in the sample;

[0066] (5) After heat treatment, two γ' phases of different sizes are formed in the sample, but their sizes are obviously refined;

[0067] (6) After heat treatment, aging twins with a size of about 380 nm were formed in the sample;

[0068] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results showed that the yield strength was 1281 MPa, the tensile strength was 1609 MPa, the strength was significantly improved, and the elongation was 16.6%. The comprehensive mechanical properties were significantly better than those of the same grade and type of alloys.

[0069] Embodiment three:

[0070] (1) All raw materials were mixed and René104ScY alloy powder was prepared by a tightly coupled argon atomization system. The crucible was a graphite crucible, the melting temperature was 1600-1650°C, the temperature was kept constant for 10-20 min, and the gas pressure was 3-5 MPa. A vibration screening device was used to screen out René104ScY alloy powder with a particle size of 15-74 μm for laser additive manufacturing. The layer thickness was controlled to be 40 μm, the laser power was 350 W, the scanning rate was 800 mm / s, the interlayer rotation angle was 67°, and a serpentine scanning strategy was adopted.

[0071] The prepared René104ScY alloy powder comprises the following components in terms of mass percentage:

[0072] Co: 21.5±0.1wt.%, Cr: 13.0±0.1wt.%, Mo: 3.8±0.1wt.%, Ti: 3.9±0.1wt.%, Al: 3.35±0.05wt.%, Ta: 2.25±0.05wt.%, W: 3.4±0.1wt.%, Nb: 0.9±0.1wt.%, C: 0.045±0.015wt.%, Zr: 0.05±0.01wt.%, B: 0.03±0.01wt.%, Sc+Y is 0.007±0.001wt.% (the molar ratio of Sc:Y is 1:1), and the balance is Ni;

[0073] (2) The prepared printed sample was sealed in a vacuum tube and subjected to solution treatment at 1200°C. The temperature was increased at a rate of 5°C / min and kept at this temperature for 1 h. The sample was then taken out and cooled to room temperature.

[0074] (3) The solution treated samples were then subjected to a double-stage aging heat treatment at 843°C / 4 h + 760°C / 8 h. After the treatment, the samples were taken out and cooled to room temperature.

[0075] (4) After heat treatment, larger equiaxed crystals were formed in the sample;

[0076] (5) After heat treatment, a uniform single-size γ' phase is formed in the sample, but its size is further refined;

[0077] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results showed that the yield strength was 1152 MPa, the tensile strength was 1409 MPa, the strength was significantly improved, the elongation was 6.4%, and the comprehensive mechanical properties were significantly better than those of the same grade and type of alloys.

[0078] Comparative Example 1:

[0079] (1) All raw materials were mixed and René104ScY alloy powder was prepared by a tightly coupled argon atomization system. The crucible was a graphite crucible, the melting temperature was 1600-1650°C, the temperature was kept constant for 10-20 min, and the gas pressure was 3-5 MPa. A vibration screening device was used to screen out René104ScY alloy powder with a particle size of 15-74 μm for laser additive manufacturing. The layer thickness was controlled to be 40 μm, the laser power was 350 W, the scanning rate was 800 mm / s, the interlayer rotation angle was 67°, and a serpentine scanning strategy was adopted.

[0080] The prepared René104ScY alloy powder comprises the following components in terms of mass percentage:

[0081] Co: 21.4~21.6wt.%, Cr: 12.9~13.1wt.%, Mo: 3.7~3.9wt.%, Ti: 3.8~4.0wt.%, Al: 3.3~3.4wt.%, Ta: 2.2~2.3wt.%, W: 3.3~3.5wt.%, Nb: 0.8~1.0wt.%, C: 0.03~0.06wt.%, Zr: 0.04~0.06wt.%, B: 0.02~0.04wt.%, Sc and Y are 0.006~0.08wt.% (Sc:Y is 1:1), and the balance is Ni.

[0082] (2) The prepared printed sample was sealed in a vacuum tube and solution treated at 1140°C. The temperature was increased at a rate of 5°C / min and kept at this temperature for 1 h. The sample was then taken out and cooled to room temperature.

[0083] (3) The solution treated samples were then subjected to a double-stage aging heat treatment at 843°C / 4 h + 760°C / 8 h. After the treatment, the samples were taken out and cooled to room temperature.

[0084] (4) After heat treatment, columnar crystals parallel to the construction direction are still retained in the sample;

[0085] (5) After heat treatment, two γ' phases of different sizes are formed in the sample, but the size of the γ' phase is significantly increased compared with the present invention;

[0086] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results showed that the yield strength was 1195 MPa, the tensile strength was 1400 MPa, the strength was significantly improved, and the elongation was 1.1%.

[0087] Comparative Example 2:

[0088] (1) All raw materials were mixed and René104ScY alloy powder was prepared by a tightly coupled argon atomization system. The crucible was a graphite crucible, the melting temperature was 1600-1650°C, the temperature was kept constant for 10-20 min, and the gas pressure was 3-5 MPa. A vibration screening device was used to screen out René104ScY alloy powder with a particle size of 15-74 μm for laser additive manufacturing. The layer thickness was controlled to be 40 μm, the laser power was 350 W, the scanning rate was 800 mm / s, the interlayer rotation angle was 67°, and a serpentine scanning strategy was adopted.

[0089] The prepared René104ScY alloy powder comprises the following components in terms of mass percentage:

[0090] Co: 21.4~21.6wt.%, Cr: 12.9~13.1wt.%, Mo: 3.7~3.9wt.%, Ti: 3.8~4.0wt.%, Al: 3.3~3.4wt.%, Ta: 2.2~2.3wt.%, W: 3.3~3.5wt.%, Nb: 0.8~1.0wt.%, C: 0.03~0.06wt.%, Zr: 0.04~0.06wt.%, B: 0.02~0.04wt.%, Sc and Y are 0.006~0.08wt.% (Sc:Y is 1:1), and the balance is Ni.

[0091] (2) The prepared printed sample was sealed in a vacuum tube and solution treated at 1180°C. The temperature was increased at a rate of 5°C / min and kept at this temperature for 1 h. The sample was then taken out and cooled to room temperature.

[0092] (3) The solution treated sample was then subjected to aging heat treatment at 843 °C / 12 h and then cooled to room temperature.

[0093] (4) After heat treatment, columnar crystals parallel to the construction direction are still retained in the sample;

[0094] (5) After heat treatment, two γ' phases of different sizes are formed in the sample, but the size of the γ' phase is significantly increased compared with the present invention;

[0095] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results showed that the yield strength was 1195 MPa, the tensile strength was 1400 MPa, the strength was significantly improved, and the elongation was 1.1%.

[0096] Comparative Example 3

[0097] Other conditions are the same as those in Example 2, except that:

[0098] (3) The solution treated sample was then subjected to a double-stage aging heat treatment at 815°C / 8 h+760°C / 8 h. After the procedure was completed, the sample was taken out and cooled to room temperature.

[0099] After heat treatment, columnar crystals parallel to the construction direction are still retained in the sample;

[0100] After heat treatment, two different sizes of γ' phases are formed in the sample, but compared with the present invention, the size of the γ' phase is significantly increased;

[0101] The mechanical properties of the heat-treated nickel-based high-temperature alloy were tested, and the results were as follows: the yield strength was 1184 MPa, the tensile strength was 1398 MPa, the strength was significantly improved, and the elongation was 6.5%. It can be seen from Comparative Example 3 and Example 2 that during double-stage aging, a slight temperature difference will seriously affect the strength and elongation of the product after aging.

Claims

1. A method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy, characterized in that: The nickel-based high-temperature alloy is a René 104 alloy containing Sc and Y, and the René 104 alloy containing Sc and Y is prepared by laser additive manufacturing technology using René 104ScY alloy powder as a raw material; the mass percentages of Sc and Y in the René 104 alloy containing Sc and Y are 0.005wt.% to 0.01wt.% respectively; The laser additive manufacturing is: Step 1: Using René104ScY alloy powder with designed composition as raw material, a printed product is prepared by laser powder bed fusion (PBF-LB) process; forming is performed by adopting the optimal process parameters of PBF-LB: controlling the laser input power to be 200-400 W, preferably 320-400 W, and more preferably 345-355 W, controlling the scanning speed to be 200-1200 mm / s, preferably 750-1200 mm / s, and more preferably 780-820 mm / s, the layer thickness to be 35-60 μm, and the rotation angle between adjacent layers to be 67°; Step 2: taking the obtained printed product as the treatment object, performing a solid solution treatment at 1160-1220° C., preferably 1160-1200° C., for 50-240 min to obtain a solid solution product; Step 3: Taking the obtained solid solution product as the treatment object, the solid solution product is subjected to aging treatment, and the aging conditions are: first aging treatment at a temperature of 830-850°C for 200-280min, cooling with the furnace to 755-765°C and then keeping the temperature for 450-500min to obtain an aged product.

2. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: The preparation method of the selected René104ScY alloy raw material powder is as follows: According to the designed components, various raw materials are prepared, all raw materials are mixed, and alloy powder is prepared by a tightly coupled argon atomization system. The crucible is a graphite crucible, the melting temperature is 1600-1650°C, and the temperature is kept constant for 10-20 minutes. The gas pressure is 3-5 MPa; a vibration screening device is used to screen out René104ScY alloy powder with a particle size range of less than 100 μm, preferably 15-74 μm, as powder for laser additive manufacturing; Preferably, Al-Sc master alloy is used to introduce Sc, and other raw materials can be single metals or master alloys.

3. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: The René104Sc alloy raw material powder comprises the following components in terms of mass percentage: Co: 21.4~21.6wt.%, Cr: 12.9~13.1wt.%, Mo: 3.7~3.9wt.%, Ti: 3.8~4.0wt.%, Al: 3.3~3.4wt.%, Ta: 2.2~2.3wt.%, W: 3.3~3.5wt.%, Nb: 0.8~1.0wt.%, C: 0.03~0.06wt.%, Zr: 0.04~0.06wt.%, B: 0.02~0.04wt.%, Sc+Y is 0.006~0.08wt.%, and the balance is Ni, and in molar ratio, Sc:Y is 1:

1.

4. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: The René104ScY alloy powder with designed composition was used as raw material powder, and the printed product was produced by PBF-LB process. The optimal process parameters of PBF-LB were adopted for forming: laser power 350 W, scanning rate 800 mm / s, layer thickness 40 μm, serpentine scanning strategy, and the rotation angle between adjacent layers was 67°.

5. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: In step 2, the printed product is treated as a treatment object, and a solid solution treatment is performed at 1175-1185° C. for 60-120 min to obtain a solid solution product.

6. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 5, characterized in that: The solid solution product was subjected to aging treatment under the following aging conditions: first, aging treatment was performed at 843°C for 4 h, then furnace cooled to 760°C and kept at this temperature for 8 h to obtain an aged product.

7. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: After the double-stage aging treatment, the obtained product contains a multi-scale heterogeneous structure consisting of bimodal size distribution grains, nano-second phases and nano-crystalline defects.

8. The method for preparing a high-strength and plastic additively manufactured nickel-based high-temperature alloy according to claim 1, characterized in that: After solution treatment at 1160℃ and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1152 MPa, a tensile strength of 1464 MPa, and an elongation of 3.2%. After solution treatment at 1180℃ and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1281 MPa, a tensile strength of 1609 MPa, and an elongation of 16.6%. After solution treatment at 1200℃ and double-stage aging heat treatment at 843℃ / 4 h+760℃ / 8 h, the alloy has a yield strength of 1152 MPa, a tensile strength of 1409 MPa and an elongation of 6.4%.

Citation Information

Patent Citations

  • A method for improving the mechanical properties of 3D-printed nickel-based superalloys through in-situ heat treatment

    CN112008079B

  • Method for improving mechanical property of 3D printing nickel-based superalloy through in-situ heat treatment

    CN112008079A

  • Additive manufacturing nickel-based superalloy with low cracking sensitivity

    CN117737505A

  • Additive manufacturing nickel-based superalloy heat treatment process

    CN118635530A

  • Method of controlling and refining final grain size in supersolvus heat treated nickel-base superalloys

    US20100329883A1